2015
DOI: 10.1016/j.semcdb.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

MYC and metabolism on the path to cancer

Abstract: The MYC proto-oncogene is frequently deregulated in human cancers, activating genetic programs that orchestrate biological processes to promote growth and proliferation. Altered metabolism characterized by heightened nutrients uptake, enhanced glycolysis and glutaminolysis and elevated fatty acid and nucleotide synthesis is the hallmark of MYC-driven cancer. Recent evidence strongly suggests that Myc-dependent metabolic reprogramming is critical for tumorigenesis, which could be attenuated by targeting specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
251
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(270 citation statements)
references
References 100 publications
12
251
0
2
Order By: Relevance
“…Because of the possible correlation between "stemness" and metabolism, we analyzed the glycolytic activity of GS cells. The metabolic function of Myc is context-dependent; Myc is implicated in glycolysis but is also involved in mitochondrial biogenesis and oxygen consumption (Hsieh et al 2015). Therefore, we analyzed the glycolytic activity of GS cells and found that Myc double-knockout GS cells have reduced glycolytic activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the possible correlation between "stemness" and metabolism, we analyzed the glycolytic activity of GS cells. The metabolic function of Myc is context-dependent; Myc is implicated in glycolysis but is also involved in mitochondrial biogenesis and oxygen consumption (Hsieh et al 2015). Therefore, we analyzed the glycolytic activity of GS cells and found that Myc double-knockout GS cells have reduced glycolytic activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because Myc is involved in glycolysis as well as mitochondrial biogenesis (Hsieh et al 2015), we reasoned that SSCs and progenitors balance these metabolic pathways differently, which might disturb the frequency of self-renewal division. We used a Seahorse extracellular flux analyzer to measure two metabolic parameters: the oxygen consumption rate (OCR) and extracellular acidification rate (ECAR).…”
Section: Defective Glycolysis Of Myc Double-knockout Gs Cellsmentioning
confidence: 99%
“…MYC/PGC1a axis in pancreatic ductal adenocarcinoma MYC-driven metabolic reprogramming is critical for cancer cell survival and proliferation (77,78). Most recently, MYC has been confirmed to be a direct regulator of PGC1a in pancreatic ductal adenocarcinoma (PDAC; ref.…”
Section: Pgc1a/erra Axis In Breast Cancermentioning
confidence: 99%
“…19 c-Myc is involved in regulating glycolytic genes and thus enhancing glycolysis. 21 Its overexpression has the effect of addicting cancer cells to glucose or glutamine, without which the cells die. 22 Emerging evidence suggests that cancer is a metabolic disease, and what has been learned about the Warburg effect indicates that malignant cells rely on glycolysis as their major energy source.…”
Section: Introductionmentioning
confidence: 99%